PENGARUH PENGENDALIAN BIAYA, TARIF LAYANAN, DAN PENDAPATAN OPERASIONAL TERHADAP PROFITABILITAS DENGAN BREAK EVEN POINT (BEP) SEBAGAI INTERVENING VARIABLE PADA KLINIK PRATAMA PT NUSANTARA SEBELAS MEDIKA - Tjahjaningastoeti, Roosnindya; Priyawan, Sunu; Ridwan, M. Sihab (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2019)
The purpose of this study is to analyze the control of costs, service rates, operating income against BEP and profitability. The population in this study was the population in this study were Primary Clinical Units in PT Nusantara Sebelas Medika totaling 6 (six) units, using saturated sampling techniques, this study used all populations to be the study sample. To test the truth of this research hypothesis, Partial Least Square (PLS) Analysis was used. The results in this study are the effect of cost control on BEP has a significant effect on the direction of positive relationships. The effect of service rates on BEP shows that the proposed hypothesis has a significant effect on the direction of negative relations. The effect of operating income on BEP shows that the proposed hypothesis has a significant effect on the direction of a positive relationship. The effect of cost control on profitability that the proposed hypothesis has no significant effect and is not supported by the direction of positive relations. The effect of service rates on profitability shows that the proposed hypothesis has insignificant effect and is not supported by the direction of negative relations. The effect of operating income on profitability that the proposed hypothesis has a significant effect on the direction of a positive relationship. The effect of BEP on profitability shows that the proposed hypothesis has a significant effect on the direction of the negative relationship.